2015
DOI: 10.1364/ao.54.003498
|View full text |Cite
|
Sign up to set email alerts
|

Field of view advantage of conjugate adaptive optics in microscopy applications

Abstract: The imaging performance of an optical microscope can be degraded by sample-induced aberrations. A general strategy to undo the effect of these aberrations is to apply wavefront correction with a deformable mirror (DM). In most cases the DM is placed conjugate to the microscope pupil, called pupil adaptive optics (AO). When the aberrations are spatially variant an alternative configuration involves placing the DM conjugate to the main source of aberrations, called conjugate AO. We provide a theoretical and expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 28 publications
6
88
0
1
Order By: Relevance
“…More recently, this same principle of conjugate AO has made its way to the microscopy community. Reports in both simulation [6][7][8] and experiment [9][10][11][12][13] have demonstrated the FOV advantage of conjugate AO as well as its feasibility. For example, conjugate AO has been applied in scanning microscopy configurations using both one- 9 and twophoton 10,11 microscopy.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…More recently, this same principle of conjugate AO has made its way to the microscopy community. Reports in both simulation [6][7][8] and experiment [9][10][11][12][13] have demonstrated the FOV advantage of conjugate AO as well as its feasibility. For example, conjugate AO has been applied in scanning microscopy configurations using both one- 9 and twophoton 10,11 microscopy.…”
Section: Introductionmentioning
confidence: 92%
“…It has also been applied in widefield (i.e., nonscanning) microscopy configurations with transillumination geometries. 12,13 The last of these involved the use of an extended-source wavefront sensor where the transillumination itself served to determine the wavefront aberrations, obviating the need for a "guide star" within the sample. While in principle this same wavefront sensor could be applied in a fluorescence microscopy application, making use of the sample fluorescence itself as the illumination source to measure wavefront aberrations, we found this difficult to implement in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume wavefront aberrations were measured from different directions using multiple wavefront sensors. 121 However, although simulations have shown that microscopy will also benefit from multiconjugate adaptive optics, [122][123][124] directly applying this approach to microscopy has proven to be difficult, despite the improvements it would provide. This is primarily because it is not straightforward to separate aberrations from different layers in highly turbid media.…”
Section: Enlarging the Corrected Field Of Viewmentioning
confidence: 99%
“…Deep-tissue imaging faces the similar problem, and others have worked in this area of research showing that correction in conjugated-image planes is also possible for microscopy applications (33)(34)(35)(36).…”
mentioning
confidence: 99%